1, 25(OH)2D3 regulates the proangiogenic activity of pericyte through VDR‐mediated modulation of VEGF production and signaling of VEGF and PDGF receptors. Issue 7 (21st May 2019) - Jamali, Nasim; Song, Yong‐Seok; Sorenson, Christine M.; Sheibani, Nader
Abstract: We have previously demonstrated that the active form of vitamin D (calcitriol; 1, 25(OH)2 D3 ) is a potent inhibitor of retinal neovascularization. However, the underlying molecular and cellular mechanisms involved remained poorly understood. Perivascular supporting cells including pericytes (PC) play important roles during angiogenesis, vascular maturation, and stabilization of blood vessels. How 1, 25(OH)2 D3 affects retinal PC proliferation and migration, and whether these effects are mediated through vitamin D receptor (VDR), are unknown. Here, we determined the impact of 1, 25(OH)2 D3 on retinal PC prepared from wild‐type (Vdr+/+) and VDR‐deficient (Vdr−/−) mice. Retinal PC expressed significantly higher VDR levels compared to retinal endothelial cells (EC). Unlike retinal EC, 1, 25(OH)2 D3 significantly decreased PC proliferation and migration and resulted in a G0 /G1 cell cycle arrest. Although 1, 25(OH)2 D3 did not inhibit the proliferation of Vdr−/− PC, it did inhibit their migration. PC adhesion to various extracellular matrix (ECM) proteins and ECM production were also affected by incubation of PC with 1, 25(OH)2 D3 . Vdr−/− PC were more adherent compared with Vdr+/+ cells. Mechanistically, incubation of Vdr+/+ PC with 1, 25(OH)2 D3 resulted in an increased expression of vascular endothelial growth factor (VEGF) and attenuation of signaling through VEGF‐R2 and platelet‐derived growth factor receptor‐beta. Incubation with soluble VEGF‐R1 (sFlt‐1) partially reversed the effect of VEGF on Vdr+/+ PC. In addition, incubation of Vdr+/+ PC with VEGF or inhibition of VEGF‐R2 increased VDR expression. Together, these results suggest an important role for retinal PC as a target for vitamin D and VDR action for attenuation of angiogenesis.